The duration of hyaluronidase and optimal timing of hyaluronic acid (HA) filler reinjection after hyaluronidase injection. (2nd January 2018) - Kim, H. J.; Kwon, S. B.; Whang, K. U.; Lee, J. S.; Park, Y. L.; Lee, S. Y.
ABSTRACT: Background : Hyaluronidase injection is a commonly performed treatment for overcorrection or misplacement of hyaluronic acid (HA) filler. Many patients often wants the HA filler reinjection after the use of hyaluronidase, though the optimal timing of reinjection of HA filler still remains unknown.Objectives : To provide the optimal time interval between hyaluronidase injections and HA filler reinjections.Methods : 6 Sprague–Dawley rats were injected with single monophasic HA filler. 1 week after injection, the injected sites were treated with hyaluronidase. Then, HA fillers were reinjected sequentially with differing time intervals from 30 minutes to 14 days. 1 hour after the reinjection of the last HA filler, all injection sites were excised for histologic evaluation.Results : 3 hours after reinjection of HA filler, the appearance of filler material became evident again, retaining its shape and volume. 6 hours after reinjection, the filler materials restored almost its original volume and there were no significant differences from the positive control.Conclusions : Our data suggest that the hyaluronidase loses its effect in dermis and subcutaneous tissue within 3–6 hours after the injection and successful engraftment of reinjected HA filler can be accomplished 6 hours after the injection.